The Use of Google Classroom Learning Management System as a Medium for Learning Arabic - Dr K M A AHAMED ZUBAIR (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study aims to describe the use of the Learning Management System (LMS) Google Classroom as a medium for teaching Arabic. It explores its historical development, key features, advantages, disadvantages, and practical application in the learning process. Employing a qualitative descriptive approach through library research, data were gathered from various written sources, including articles, scientific journals, and documents discussing the use of Google Classroom in online learning. The data were analyzed descriptively by reviewing, recording, and organizing relevant literature. The findings indicate that Google Classroom facilitates teachers in managing classes, sharing materials, assigning tasks, and conducting assessments online. The platform supports the mastery of the four Arabic language skills-istima’ (listening), kalam (speaking), qira’ah (reading), and kitabah (writing)-through interactive features integrated with other Google services (Linux & Daulay, 2023; Rini, Maswan, & Sugiarto, 2021). However, challenges such as limited internet access, low digital literacy, and reduced direct interaction remain obstacles. These require mitigation through creative and collaborative learning strategies to enhance the effectiveness of Arabic language learning in the digital era.